Diagnosis Approach of Endobronchial Tuberculosis: Literature Review - Ginting, Mario Oktafiendi; Indriani, Sri Indah; Simatupang, Elvando Tunggul Mauliate (Indonesian Journal of Tropical and Infectious Disease, 2025)
Pulmonary tuberculosis (PTB) remains a global health problem and the leading cause of death from infectious diseases. Indonesia as an endemic country and the second highest contributor of PTB cases in the world provides support and attention to PTB case finding and treatment success. Endobronchial tuberculosis (EBTB) is problematic PTB because the lesions are often not detected by sputum examination and chest X-ray. Clinically, there is no significant difference in symptoms between TB and EBTB. In general, EBTB gives a more severe clinical appearance due to airway stenosis. Bronchoscopy and thoracic computed tomography scan (CT scan), along with microbiological investigations, are the most useful diagnostic tools for confirming and evaluating tracheobronchial stenosis. In addition, bronchoscopy can also be used as a longterm treatment in cases of EBTB due to airway stenosis. The goals of treatment are the eradication of Mycobacterium tuberculosis (Mtb) bacilli with antituberculosis drugs (ATD) and the prevention of airway stenosis. Intervention of bronchoscopic techniques and surgery are required for those patients who develop severe tracheobronchial stenosis that causes significant symptoms, including dyspnea, repeated post-obstructive pneumonia or bronchiectasis. The most common complications of EBTB are airway stenosis, atelectasis, hemoptysis and shortness of breath accompanied by wheezing despite the administration of ATD. Bronchoscopic intervention can support the acceleration of EBTB treatment, prevent repeated hospitalizations and improve the quality of life of patients. Acceleration of diagnosis and administration of ATDs in a complete and routine way is expected to reduce morbidity and even mortality rates in EBTB cases.